If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3d + 8 = 2d + -7 Reorder the terms: 8 + -3d = 2d + -7 Reorder the terms: 8 + -3d = -7 + 2d Solving 8 + -3d = -7 + 2d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-2d' to each side of the equation. 8 + -3d + -2d = -7 + 2d + -2d Combine like terms: -3d + -2d = -5d 8 + -5d = -7 + 2d + -2d Combine like terms: 2d + -2d = 0 8 + -5d = -7 + 0 8 + -5d = -7 Add '-8' to each side of the equation. 8 + -8 + -5d = -7 + -8 Combine like terms: 8 + -8 = 0 0 + -5d = -7 + -8 -5d = -7 + -8 Combine like terms: -7 + -8 = -15 -5d = -15 Divide each side by '-5'. d = 3 Simplifying d = 3
| X+x-6=20 | | 2(2.3d-3)=-5.494 | | 8y+11=2y-29 | | -50-9x=8x-18 | | (-2-7)[5-(8.5)]= | | 5x+8=64-7x | | H^2+16h+15=0 | | 4d-11=2d-7 | | 19x-4y+6-7x-3-2y= | | 44-6x=12x+20 | | 5x+11=311-9x | | -2(3y-6)+3=21 | | x^2(a-b)-(a-b)=0 | | 4d-11=7d-7 | | 1n-12=3n | | 81x-5=8x+16 | | 5x-7+2x+3=10 | | 0=4.9x^2-28x | | 4(a+3)=12+4a | | (2x-2)+3x=0 | | 3s-4(1+3s)=8+3s | | 5x+4x=8x+12 | | (2x-2)+3x= | | 218-2x=43x+18 | | 6(n+1)= | | 10-9x=58-30x | | (y+5)(y-1)=0 | | (x-11)=9 | | -5(2x+1)=-15 | | 2onehalfx=-16 | | 14x-5x+6=12 | | 125+X^3=0 |